India's 1990-91 Crisis: Reforms, Myths and Paradoxes - Planning Commission (Planning Commission Government of India, 2001)
The 1990-91 economic crisis in India, triggered by political instability, external shocks such as the Gulf War, and rising fiscal and trade deficits, prompted a comprehensive set of economic reforms that reshaped the country’s macroeconomic framework. The crisis culminated in a severe balance of payments deficit, necessitating urgent policy interventions. Key reforms included fiscal consolidation, an 18% nominal depreciation of the rupee, dismantling of import controls, reduction of tariffs, and liberalization of foreign direct investment. The introduction of the Liberalised Exchange Rate Management System (LERMS) and measures to enhance currency convertibility further strengthened India’s external sector, improving trade and investment flows while curbing informal foreign exchange activities. These reforms increased economic openness, bolstered investor confidence, and initiated a period of sustained growth, although trade and FDI remained small relative to GDP. The report highlights the domestic intellectual contributions to policy design, dispelling myths that reforms were solely externally driven, and underscores the need for continued structural reforms, infrastructural investment, and trade openness to consolidate India’s position in the global economy.
Planning Commission Government of India December, 2001
Keywords: India; 1990-91 Crisis; Economic Reforms; Balance of Payments; Fiscal Deficit; Trade Liberalization; Foreign Direct Investment; Rupee Depreciation; LERMS; Currency Convertibility; Gold Import Policy; Structural Adjustment